Definitive palliation with cavopulmonary or aortopulmonary shunts for adults with single ventricle physiology. Issue 1 (1st January 2000) - Gatzoulis, M A; Munk, M-D; Williams, W G; Webb, G D
Abstract : OBJECTIVE: To compare the relative merits of cavopulmonary or aortopulmonary shunts, or both, as definitive non-Fontan palliations for patients with single ventricle physiology. DESIGN: Clinical data, ECG, echocardiographic data, surgical records, and available postmortem material were reviewed in all patients with single ventricle physiology identified from the University of Toronto Congenital Cardiac Centre for Adults (UTCCCA) database who had not undergone a Fontan operation. Current status of patients was assessed from clinic reviews and patient contact. Two groups of patients were identified: those with cavopulmonary shunt (group 1, n = 35); and those with aortopulmonary shunt(s) only (group 2, n = 15). RESULTS: 50 adults (21 male/29 female) who underwent the last palliation at a median age of 11 years (range 1 day to 53 years) were identified. During a mean (SD) follow up of 13.0 (6.2) years at the UTCCCA, 19 patients died. Survival is 89.4% and 51.9% at 10 and 20 years, respectively, from the time patients were first seen at UTCCCA, with no differences between the groups. Most recent New York Heart Association (NYHA) classification was I–II in 21 patients, III in 25, and IV in four patients; mean haemoglobin was 190 (28) g/l, and oxygen saturation was 82 (4)%, with no group differences. Arrhythmia developed in 25 patients (atrial flutter/fibrillation in 20 and/or sustained ventricular tachycardia in 11). Atrial flutter/fibrillation was more common in patients in group 2, who also showed a greater decline in ventricular function with time. Age at last palliation, cardiothoracic ratio, and inclusion in group 2 were predictive of atrial flutter/fibrillation, poor ventricular function predictive of ventricular tachycardia, NYHA class > III, and prior ventricular tachycardia predictive of death. CONCLUSIONS: Cavopulmonary or aortopulmonary shunts, or both, provide sustained palliation for selected patients with single ventricle physiology. Survival for both compares favourably with published Fontan series. Compared to aortopulmonary shunts, cavopulmonary shunts convey a beneficial long term effect on ventricular function. Arrhythmia is a major cause of late morbidity in these patients, relating to both ventricular dysfunction and death. Onset of sustained ventricular tachycardia is an ominous sign.